Unravelling stress responsive NAC1 gene (OsNAC1) from potential Indonesia and Vietnam local varieties rice - Zulheri, N.; Duong, V. N.; Ifan, A. C.; Indah, A.; Yen, T. V.; Quyen, T. V.; Asmah, I. (International Journal of Agricultural Technology, 2024)
The wide coastal area of rice production is reached 76.94% which showed the percentage of areas with high salinity constraints in Indonesia and Vietnam. The result was approximately 200 sequences from all samples which was similar to Oryza sativa Japonica Group NAC domain containing protein 92 (LOC4336052) transcribed transcript variant X2, mRNA (XM_015778438.2) for percentage of 95 – 98%. The conclusion confirmed that OsNAC1 gene from eleven genotype was someone similar evident by Phylogenetic construction result.